Right ventricular sex differences in patients with idiopathic pulmonary arterial hypertension characterised by magnetic resonance imaging: pair-matched case controlled study. - Andrew J Swift; Dave Capener; Charlotte Hammerton; Steven M Thomas; Charlie Elliot; Robin Condliffe; Jim M Wild; David G Kiely (PLoS ONE, 2015)
Sex differences exist in both the prevalence and survival of patients with idiopathic pulmonary arterial hypertension (IPAH). Men are less frequently affected by the condition but have worse outcome as compared to females. We sought to characterise the sex related differences in right ventricular remodelling in age matched male and female patients with IPAH using cardiac magnetic resonance imaging (MRI).A case controlled pair-matched study was conducted with patients matched by age and sex. Steady state free precession (SSFP) MRI of the heart was performed at 1.5T. Cardiac volume, function and mass measurements were corrected for age, sex and BSA according to reference data.40 age and sex matched patients with IPAH were identified. The mean age was 57 (SD 17) in both male and female cohorts. Men had proportionally lower right ventricular (RV) ejection fraction, RV stroke volume and LV stroke volume than females, p=0.028, p=0.007 and p=0.013, respectively. However, there was no significant difference in RV mass or haemodynamic indices of mPAP and PVR between males and females.Male patients with IPAH have proportionally worse RV function despite similar afterload. We hypothesise that adaptive remodelling of the RV in response to increased afterload in IPAH is more effective in females.